Lorca in Pictures. El paseo de Buster Keaton (Castilla. Estudios de Literatura, 2014)
El paseo de Buster Keaton, by Federico García Lorca, is a dramatic piece, short and experimental but provided with a prolific symbolism. It is part of what is called by the literary criticism “teatro imposible” and has been considered as a perfect example of surrealism applied to drama. This study follows the trail of each one of the symbols of the text in connection with the rest of the New York author’s work. Our dissertation goes beyond the main thesis defended in El paseo: the finger pointing of materialism and the defence of Nature.
Keywords: García Lorca; Buster Keaton; simbology; Yorker cycle; materialism; nature